Microbial community differentiation in vent chimneys of the Lost City Hydrothermal Field reflects habitat heterogeneity - Alian, Osama M.; Brazelton, William J.; Aquino, Karmina A.; Twing, Katrina I.; Pendleton, H. Lizethe; Früh-Green, Gretchen; Lang, Susan Q.; Schrenk, Matthew O. (Frontiers in Microbiomes, 2025)
Oceanic hydrothermal vent systems represent some of the oldest habitats on Earth and serve as analogs for extraterrestrial environments. The Lost City Hydrothermal Field (LCHF) near the Mid-Atlantic Ridge is one such environment, and its large chimneys are unique in hosting actively venting hydrothermal fluids that are primarily controlled by serpentinization reactions in the subseafloor. Microbial communities within LCHF have been studied for insights into their functional adaptations to the warm, alkaline, and dissolved inorganic carbon-limited environment. Metagenomic and mineralogical data collected during a recent expedition to Lost City were analyzed to delineate associations between microbial populations and physical, chemical and biological characteristics of the chimneys. Bacterial 16S rRNA gene sequences show a high degree of putative microdiversity within the relatively dominant genera Desulfotomaculum, Sulfurovum, Thiomicrorhabdus, and Serpentinicella, which represent a large core of the overall LCHF vent bacterial community. This microdiversity relates to the compositional fraction of aragonite, brucite, and calcite minerals within chimney samples rather than just the composition of nearby vent fluids. Although many species are found in both chimneys and venting fluids, the overall microbial community structures in chimney biofilms remain distinct from the hydrothermal fluids that flow through them. Shotgun metagenomic analyses reveal differences among genes predicted to be involved in carbon, methane, nitrogen and sulfur cycling with respect to their correlations to the abundances of specific minerals. These data hint at microenvironmental complexity lost within standard bulk analyses. The findings of this study underscore the need to more closely examine microbe-mineral interactions in natural environments, critically informing not just population-level distributions, but also the functional underpinnings of these extremophile microbial communities.